Implementing the NHS information technology programme: qualitative study of progress in acute trusts. Issue 7608 (17th May 2007) - Hendy, Jane; Fulop, Naomi; Reeves, Barnaby C; Hutchings, Andrew; Collin, Simon
Abstract : Objectives To describe progress and perceived challenges in implementing the NHS information and technology (IT) programme in England. Design Case studies and in-depth interviews, with themes identified using a framework developed from grounded theory. We interviewed personnel who had been interviewed 18 months earlier, or new personnel in the same posts. Setting Four NHS acute hospital trusts in England. Participants Senior trust managers and clinicians, including chief executives, directors of IT, medical directors, and directors of nursing. Results Interviewees unreservedly supported the goals of the programme but had several serious concerns. As before, implementation is hampered by local financial deficits, delays in implementing patient administration systems that are compliant with the programme, and poor communication between Connecting for Health (the agency responsible for the programme) and local managers. New issues were raised. Local managers cannot prioritise implementing the programme because of competing financial priorities and uncertainties about the programme. They perceive a growing risk to patients' safety associated with delays and a loss of integration of components of the programme, and are discontented with Choose and Book (electronic booking for referrals from primary care). Conclusions We recommend that the programme sets realistic timetables for individual trusts and advises managers about interim IT systems they have to purchase because of delays outside their control. Advice needs to be mindful of the need for trusts to ensure longer term compatibility with the programme and value for money. Trusts need assistance in prioritising modernisation of IT by, for example, including implementation of the programme in the performance management framework. Even with Connecting for Health adopting a different approach of setting central standards with local implementation, these issues will still need to be addressed. Lessons learnt in the NHS have wider relevance as healthcare systems, such as in France and Australia, look to realise the potential of large scale IT modernisation.